Planktonic Foraminifera Biostratigraphy Of Taeno Limestone, Ambon, Maluku Province, Indonesia - Zulfiah; Aponno, Sanny V.; Elly, Erfin (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The limestone became exposed to the surface because of an uplift event during the Quaternary period. This study aims to determine the age of limestone outcrops in the Taeno Traverse using planktonic foraminifera. This research located in Negeri Rumah Tiga, Teluk Ambon District, Ambon City. Field observations and laboratory analysis comprise the two steps of the study methodology. Employ the measuring section approach to gather detailed data in the field. There are 12 layers in the track, totaling 5.34 meters in thickness and 16.5 meters in length. Foraminifera samples prepared in the laboratory using H2O2 extraction and each sample's planktonic foraminifera taxa were identified. Nineteen samples were processed and confirmed to be fossilized planktonic foraminifera. A binocular stereo microscope with a 40x magnification used to analyze the data. The Taeno traverse is composed of calcarenite, a type of clastic limestone. The main characteristics include brownish-grey color, good sorting, sand particle size, open packing, and rounded-subrounded grain shape. Based on the identification results, 30 taxa of planktonic foraminifera fossils were found. The species with the highest abundance are Globorotalia tumida tumida, Globorotalia menardii menardii, Neogloboquadrina incompta, Pulleniatina obliquiloculata, Orbulina universa, Globigerinoides tenellus, and Spaerodinella deshiscens. According to the biodatum results, the Taeno Traverse is part of the Globorotalia ttruncatulinoides truncatulinoides zone with Globigerinella calida calida, Globorotalia tosaensis tosaensis, and Globorotalia crassaformis crassaformis sub-biozonation. This zone shows the age range of N21-N23, or equivalent to the Pleistocene.